1997
DOI: 10.1093/ajcn/65.6.1703
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat in white and African American prepubertal children

Abstract: The objectives of this study were 1) to examine interrelations among intraabdominal adipose tissue (IAAT) and other adiposity indexes, 2) to identify a visceral obesity index that is independent of total adiposity, and 3) to examine sex and ethnic (white compared with African American) differences in IAAT. We measured IAAT and subcutaneous abdominal adipose tissue (SAAT) using computed tomography, and total fat mass (FM) by dual-energy X-ray absorptiometry in a heterogenous sample of 101 children aged 7.7 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 13 publications
11
124
1
Order By: Relevance
“…Visceral adiposity is highly variable in children and is related to ethnicity. Goran et al, (1997) have shown that the relative distribution of intra-abdominal tissue compared with the subcutaneous abdominal region is significantly lower in African-American children than in whites. The effect of visceral adiposity on the metabolic complications and risk of cardiovascular disease and non-insulin dependent diabetes in adults may also vary amongst ethnic groups (Albu et al, 1997).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Visceral adiposity is highly variable in children and is related to ethnicity. Goran et al, (1997) have shown that the relative distribution of intra-abdominal tissue compared with the subcutaneous abdominal region is significantly lower in African-American children than in whites. The effect of visceral adiposity on the metabolic complications and risk of cardiovascular disease and non-insulin dependent diabetes in adults may also vary amongst ethnic groups (Albu et al, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…One potential difficulty with the waist circumference measurement will be its use across ethnic groups. Children from different populations vary in their rate of proportional growth and in fat patterning (Goran et al, 1997). Visceral adiposity is highly variable in children and is related to ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…5 ± 11,23,24 Abdominal visceral fat has recently been measured in children. 25,26 These studies have suggested that deleterious effects of visceral adipose tissue on lipidalipoprotein risk factors seen in adults are already present in children. Predicting visceral fat from anthropometric measures such as waist girth, WHR and sagittal diameter has been attempted in both adults 8,10,27 and children.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that these individuals may be at a greater risk of obesity-related morbidity. Studies in the USA (Goran et al 1997;He et al 2002b) have demonstrated ethnic differences in fat distribution among Asian, African-American and Caucasian prepubertal children. Generally, the relative distribution of adipose tissue in the intra-abdominal region compared with the subcutaneous abdominal region is significantly lower in children from African-American backgrounds compared with Caucasian children.…”
Section: Abdominal Fatness Ethnicity and Health Riskmentioning
confidence: 99%